Combining three types of data in studying attitudes to English as a Lingua Franca - Stanojević, Mateusz-Milan (2011)
Attitudes play a crucial role in studying English as a Lingua Franca (ELF) pronunciation (Jenkins 2007), including the stereotypes of interlocutors (based on their inner/outer/expanding circle accent ; e.g. Drljača Margić and Širola 2009), the accent a speaker would like to have, and the relatedness of the pronunciation self-concept to “objective” pronunciation performance (Chuming 2004). Thus, studying ELF pronunciation should combine research of attitudes/identities with actual pronunciation. We argue for a bottom-up and top-down construal of categories and their verification, based on a combination of socio-phonetic and phonetic data, within a theoretical framework flexible enough to accommodate the methodological variety into a relatively unified, natural, explicit and operationalizable model. In this paper we address the first stage of this tall order, i.e. the construction of a reliable questionnaire based on a unified theoretical framework. We combine three types of data: linguistic journals ; focus group discussions and survey results. Linguistic journals were used to explore the attitudes of individual speakers of ELF towards their English use in everyday situations. The participants (N=4) were ELF users who commented on their use of English in a seven-day period. Our qualitative analysis showed that English was used as a matter of course in a variety of situations in everyday life with native and non-native speakers. We focused on attitudes towards ELF in a focus group study (3 focus groups of 6 participants each). The study showed that native speakers were taken to have linguistic authority over non-native speakers, and that their accents were seen as prestigious. This fed into the survey administered to secondary school pupils (N=1033), university students (N=1461) and employees in a large international company (N=207). Quantitative analysis showed significant differences in ELF pronunciation attitudes varying with regard to, e.g., age, attitudes to standard Croatian, self-assessment of English pronunciation, gender, and perceived role in the exchange. The three methodologies fed into a theoretical model of stratification of ELF (Josipović Smojver and Stanojević 2010), which is the basis for a bottom-up construction of a reliable questionnaire surveying a number of factors related to ELF pronunciation (national identity, the purpose of the exchange, the (non-)native participants in the exchange, attitudes to standard pronunciation of ELF and Croatian). If our theoretical claims are validated, we need to combine the attitudes with the actual pronunciation practices, to find possible discrepancies – another bottom up stage in the theory-practice cycle. References Chuming, Wang. 2004. “A study on the relationship between English pronunciation self-concept and actual pronunciation.” Foreign Language World (5). Drljača Margić, Branka, and Dorjana Širola. 2009. “(Teaching) English as an International Language and native speaker norms: attitudes of Croatian MA and BA students of English.” English as an International Language Journal 5: 129-136. Jenkins, Jennifer. 2005. “Implementing an international approach to English pronunciation: the role of teacher attitudes and identity.” TESOL Quarterly 39 (3): 535-543. Josipović Smojver, Višnja ; Mateusz-Milan Stanojević (2010). „Stratification of ELF: identity constructions of learners and speakers“. Paper presented at: Accents 2010: Accents in teaching English across time and space. Łódź, Poland, December 9-11, 2010.